2016
DOI: 10.1371/journal.pone.0167653
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Karyotype Evolution in Lasiopodomys Involved at Least Two Autosome – Sex Chromosome Translocations

Abstract: The generic status of Lasiopodomys and its division into subgenera Lasiopodomys (L. mandarinus, L. brandtii) and Stenocranius (L. gregalis, L. raddei) are not generally accepted because of contradictions between the morphological and molecular data. To obtain cytogenetic evidence for the Lasiopodomys genus and its subgenera and to test the autosome to sex chromosome translocation hypothesis of sex chromosome complex origin in L. mandarinus proposed previously, we hybridized chromosome painting probes from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 38 publications
5
34
1
Order By: Relevance
“…Moreover, the data on C. sokolovi indicate that even within a compact genus, such as Cricetulus , variation in the rates of karyotype evolution can be substantial. Similar cases are represented by the arvicoline genera Ellobius [Romanenko et al, 2007b], Microtus (subgenus Alexandromys ) [Lemskaya et al, 2010], and Lasiopodomys [Gladkikh et al, 2016].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, the data on C. sokolovi indicate that even within a compact genus, such as Cricetulus , variation in the rates of karyotype evolution can be substantial. Similar cases are represented by the arvicoline genera Ellobius [Romanenko et al, 2007b], Microtus (subgenus Alexandromys ) [Lemskaya et al, 2010], and Lasiopodomys [Gladkikh et al, 2016].…”
Section: Discussionmentioning
confidence: 81%
“…Metaphase chromosome spreads were prepared from chromosome suspensions obtained from early passages of primary fibroblast cultures as described previously [Yang et al, 1999;Graphodatsky et al, 2000Graphodatsky et al, , 2001. C-banding was done as described by Gladkikh et al [2016]. GTG-banding was performed on chromosomes of all 4 animals prior to FISH using the standard trypsin/ Giemsa treatment procedure [Seabright, 1971].…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…To determine the location of heterochromatin, C-banding was performed per the standard technique (Sumner 1972) with some modifications, as described in Gladkikh et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Sex chromosome systems of L. m. vinogradovi have been investigated first with G-banding and routine staining [3] and recently by cross-species chromosome painting [10]. Using the last method, Gladkikh et al [10] demonstrated the origin of neo-X chromosomes by at least two independent autosome-sex chromosome translocation events. The complex of sex chromosomes in the only female (2n = 47) studied by these authors consisted of one metacentric chromosome (neo-X1), one submetacentric chromosome (neo-X2), and one small acrocentric (neo-X3).…”
Section: Introductionmentioning
confidence: 99%